2021
DOI: 10.1007/s11012-021-01431-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic closed-form solutions of FGM plates subjected to temperature change in longitudinal and thickness directions

Abstract: An closed-form solution of simply supported FGM plates under thermal loads is developed based on medium-thick plate assumption. Further to assume constant Poisson's ratio and thermal expansion coefficient, the closed-form solutions of the FGM plates with through-the-thickness Young's modulus under temperature change in x-and z-directions are evaluated, expressed in terms of the thermal axial force and thermal bending moment. The closed-form solutions confirmed by finite element analysis give a complete insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These solutions were derived for FGM plates experiencing linear temperature variations in the z-direction. Chung [3] extended the analysis to obtain closed-form solutions for FGM plates with temperature changes in both the xand z-directions. The study demonstrated that by appropriately selecting material gradation from the derived closed-form solution, the deflection of the FGM plate in the thickness direction can be effectively minimized under thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…These solutions were derived for FGM plates experiencing linear temperature variations in the z-direction. Chung [3] extended the analysis to obtain closed-form solutions for FGM plates with temperature changes in both the xand z-directions. The study demonstrated that by appropriately selecting material gradation from the derived closed-form solution, the deflection of the FGM plate in the thickness direction can be effectively minimized under thermal loading.…”
Section: Introductionmentioning
confidence: 99%